Exploring the Correlation between Emotional Intelligence and Job Satisfaction of Librarians in Public Universities in Nigeria - Abdulazeez Yaya, Japheth; Eseohe Ebunuwele, Grace (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study investigated exploring the correlation between emotional intelligence and job satisfaction of librarians in Nigerian public universities. It adopted correlational survey research design. The study population consisted of 1,254 librarians in public university libraries in Nigeria, from which 923 were selected using simple random sampling. The research instrument used was a self-developed questionnaire. A response rate of 67.2% was achieved. Data were analysed using descriptive and inferential statistics.The study revealed a significant relationship between emotional intelligence and job satisfaction (r = 0.034, P < 0.05) of librarians in public university libraries in Nigeria. The study concluded that contrary to general belief, job satisfaction and emotional intelligence levels of librarians in university libraries were high. It is recommended that university library management should continue to promote values such as improved employee recognition, good leadership style and improved human capital development programmes that would increase job satisfaction and emotional intelligence of its workforce.